An intelligent approach for project selection in construction industry - Azhar, H. Syed; Kumar, V.S.S. (Journal of Structural Engineering, 2024)
The most important objectives taken into account for project selections are economic, technical, environmental and social factors. Evaluation of a single project is easier when compared to selection of two or more projects. The decision mechanism is constrained by the uncertainty inherent in the determination of the relative importance of each attribute element. The project selections using fuzzy logic utilizes human reasoning process and make decisions based on incomplete or imprecise data. The approach is based on reducing uncertainty and the optimal alternative is obtained by the relative weights of each attributes combined over the aggregate utility function. Decision maker’s preference or utility function can be defi ned very clearly in the traditional selection process. This research shows how to deal with the project selection issues when a few or more project attributes are faced with random variations. A multi attribute utility theory is incorporated and the aggregate utility function for a project is derived as a fuzzy number which again results in probabilistic information for stochastic dominance tests.